2013
DOI: 10.1186/1472-6939-14-28
|View full text |Cite
|
Sign up to set email alerts
|

Improving understanding in the research informed consent process: a systematic review of 54 interventions tested in randomized control trials

Abstract: BackgroundObtaining informed consent is a cornerstone of biomedical research, yet participants comprehension of presented information is often low. The most effective interventions to improve understanding rates have not been identified. PurposeTo systematically analyze the random controlled trials testing interventions to research informed consent process. The primary outcome of interest was quantitative rates of participant understanding; secondary outcomes were rates of information retention, satisfaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
417
2
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(443 citation statements)
references
References 53 publications
14
417
2
10
Order By: Relevance
“…However, the bias in not remembering about signing informed consent can be explained by the fact that subjects might not understand the contents of the term (13,(18)(19)(20). Best practice already obliges researchers to comply with a range of legal and ethical obligations, with a particular focus on informed consent and research transparency (6,15,16,18,21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the bias in not remembering about signing informed consent can be explained by the fact that subjects might not understand the contents of the term (13,(18)(19)(20). Best practice already obliges researchers to comply with a range of legal and ethical obligations, with a particular focus on informed consent and research transparency (6,15,16,18,21).…”
Section: Resultsmentioning
confidence: 99%
“…The patient and his/her rights are being respected, as required by Resolution CNS 466/12 (11), since it is necessary to show all procedures, risks and benefits, which must be written in language that is accessible and understandable to the research subject (1,(13)(14)(15)(16)18). It should be noted that the person's autonomy should…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para la mejora de la comprensión del CI se desarrollaron trifoliados con dibujos comprensibles con personajes aymaras. Se llevó a cabo un trabajo conjunto entre los investigadores y la comunidad, a fin de respetar su autonomía y entablar relaciones de confianza, mutuo respeto y valorización de la cultura indígena (3,(15)(16)(17)(18).…”
Section: Tabla 5 Comprensión De Los Elementos Del Consentimiento Infunclassified
“…Efforts to improve participant comprehension in the consent process are emerging but identification of best practices or types of informed consent interventions need more research. For example, a systematic review of 54 interventions tested in randomized controlled trials found participant comprehension was improved through multi-media efforts (31%), enhanced/simplified consent forms (41%), extended discussions (50%), and comprehension assessments (33%) [32]. Current recommendations for promoting participant comprehension during the consent process are the use of simplified consent form and/or multi-media approaches.…”
Section: Education and Consent Approachesmentioning
confidence: 99%